2008
DOI: 10.1538/expanim.57.111
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Associated Complications in Spontaneously Diabetic Torii Fatty Rats

Abstract: The Spontaneously Diabetic Torii (SDT) fatty rat, established by introducing the fa allele of the Zucker fatty rat into the SDT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
105
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 24 publications
(45 reference statements)
10
105
0
Order By: Relevance
“…Body weights and serum insulin levels of the SDT-+/+ rats decreased after 16 weeks of age (Table 1). Also, the increase of renal-related parameters such as BUN, urine volume, and urinary protein, was observed in SDT-fa/fa rats, similar to results reported in previous studies (Table 1) [4,10]. In addition to these changes, increases of serum leptin and urine angiotensinogen levels were shown by the SDT-fa/fa rats (Fig.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Body weights and serum insulin levels of the SDT-+/+ rats decreased after 16 weeks of age (Table 1). Also, the increase of renal-related parameters such as BUN, urine volume, and urinary protein, was observed in SDT-fa/fa rats, similar to results reported in previous studies (Table 1) [4,10]. In addition to these changes, increases of serum leptin and urine angiotensinogen levels were shown by the SDT-fa/fa rats (Fig.…”
supporting
confidence: 89%
“…SDT-fa/fa rats exhibit hyperphagia and obesity immediately after weaning, and diabetes and its complications are found at a younger age in SDT-fa/fa rats than in SDT-+/+ rats [4,9,10,12]. However, blood pressure in SDT-fa/fa rats has not yet been examined.…”
mentioning
confidence: 99%
“…This is in line with results from clinical studies demonstrating that in addition to hyperglycemia, other metabolic factors and blood pressure are involved in the manifestation and progression of retinopathy in humans. 4,54,55 In this regard, SHR/N-cp together with other non-STZ-based rat models [56][57][58][59][60][61][62][63][64] are useful tools to dissect the complexity of causative factors and disease mechanisms contributing to the varying spectrum of diabetic retinopathy. 55 Studies in these models have indeed revealed the contrasting impairment of the retina in the presence of cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…55 Studies in these models have indeed revealed the contrasting impairment of the retina in the presence of cardiometabolic risk factors. 62,63 Intervention during an early stage of the disease is particularly important to prevent manifestations of visual deterioration. 55,65 The latter aspect underscores the value of the SHR/N-cp model, which exhibits characteristics of the early phase of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorder in SDT fatty rats was obviously promoted as compared with SDT rats [104,105]. Serum glucose levels in SDT fatty rats of both sexes were elevated from 6 weeks, and lipid parameters such as serum triglyceride and total cholesterol levels in the rats were elevated from 4 weeks of age.…”
Section: Glucose Tolerance Insulin Sensitivity and Drug Treatmentmentioning
confidence: 92%